Out-of-hospital cardiac arrest in patients without clinically significant coronary artery disease: comparison of clinical, electrophysiological, and survival characteristics with those in similar patients who have clinically significant coronary artery disease. Issue 6 (December 1987) - McLaran, C J; Gersh, B J; Sugrue, D D; Hammill, S C; Zinsmeister, A R; Wood, D L; Holmes, D R; Osborn, M J
Abstract : Fifty nine survivors of out-of-hospital cardiac arrest unassociated with an acute myocardial infarction were referred for intracardiac electrophysiological study. Thirty patients who had no clinically significant coronary artery disease (group 1) were compared with 29 who did (group 2). Ventricular tachycardia or fibrillation was induced in significantly more patients in group 2 than in group 1 (69% vs 40%). Median duration of follow up, which was achieved in all patients, was 31 months in group 1 and 14 months in group 2. In group 1, an effective treatment was identified electrophysiologically in seven patients, and none died; an arrhythmia was induced, but no effective treatment was identified in five patients, and one patient died subsequently; an arrhythmia was not induced in 18 patients, 15 of whom were treated empirically with anti-arrhythmic drugs, and one died. In group 2, effective treatment was identified electrophysiologically in seven patients and three died (two of pump failure) during follow up. In 13 an arrhythmia was induced but no effective drug was identified, and six died or had a recurrence; in another nine patients without inducible arrhythmias, six subsequently died or had a recurrence. A Cox proportional hazards analysis identified previous myocardial infarction as the only predictor of recurrence. Patients without coronary artery disease who suffer an out-of-hospital cardiac arrest have a low inducibility rate at electrophysiological study and an excellent prognosis compared with patients who have coronary artery disease. Electrophysiological testing seemed to be of value in predicting the response to antiarrhythmic drugs, but non-inducibility of arrhythmias in patients with coronary artery disease was of no predictive value.